2016
DOI: 10.1556/066.2016.45.2.18
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic and Flavonoid Content in Hericium Erinaceus, Ganoderma Lucidum, and Agrocybe Aegerita under Selenium Addition

Abstract: The phenolic and fl avonoid contents and composition and the antioxidant ability in Hericium erinaceus, Ganoderma lucidum, and Agrocybe aegerita under selenium (Se) addition to growth medium were studied. The contents of total Se in fruiting bodies of controls (0 mM of Se) were 4.58 (A. aegerita), 8.53 (G. lucidum), and 14.29 (H. erinaceus) mg kg -1 dry weight (DW), and was signifi cantly increased by Se enrichment of substrate. The total phenolics in fruiting bodies of controls of H. erinaceus, G. lucidum, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
1
19
2
3
Order By: Relevance
“…Gallic acid was the prevalent phenolic acid in the profile of H. erinaceus (21.5 lg/g DW). In comparison to our earlier study some phenolic compounds were not detected (Gąsecka et al 2016). To our knowledge, the composition of the phenolic compounds of H. erinaceus has been studied in only a few works.…”
Section: Resultscontrasting
confidence: 93%
“…Gallic acid was the prevalent phenolic acid in the profile of H. erinaceus (21.5 lg/g DW). In comparison to our earlier study some phenolic compounds were not detected (Gąsecka et al 2016). To our knowledge, the composition of the phenolic compounds of H. erinaceus has been studied in only a few works.…”
Section: Resultscontrasting
confidence: 93%
“…The total flavonoid (TFC) and phenolic (TPC) contents of H. erinaceus were quantified using the Folin-Ciocalteu reagent (Table 1). It was found that the total phenolic content of H. erinaceus reached 23.26 mg GAE/g DM and the total flavonoid content reached 3.26 mg QE/g DM with 80% ethanol concentration, extraction time of 45 min, and solvent-material ratio 30 mL/g, these data being consistent with those from other scientific studies [12,33]. In the DPPH assay, the maximum antioxidant activity of H. erinaceus corresponded to an IC 50 of 92.4 µg/mL.…”
Section: Effect Of Extraction Parameters On Tpc Tfc and Dpphsupporting
confidence: 90%
“…Erinacine A ( Figure 1) was isolated from the fungal species Hericium erinaceus; its chemical structure is deposited in PubChem with the indication 9,867,477. Mainly, the antioxidant activity of the H. erinaceus species is due to the presence of polysaccharides (β-glucans) and diterpenoids (hericenons, erinacines), but several authors have stated that there is a close link between the antioxidant activity of H. erinaceus and the presence of flavonoids and polyphenols [12,13]. It has been noted that the biosynthesis of erinacine A in submerged culture can lower production costs because the chemical synthesis of diterpenoids is a long, multistage process and provides poor yield [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In case of excessive oxidative stress, antioxidants produced in the living organism are not suffi cient and antioxidant-rich nutrients should be consumed (POLJSAK et al, 2013). It is known that mushrooms have antioxidant properties due to different compounds in their structure (BHATIA et al, 2014;GĄSECKA et al, 2016). Determination of the heavy metal level, which is one of the environmental factors responsible for oxidative stress, plays a signifi cant role in identifi cation of hazard levels for living organisms.…”
mentioning
confidence: 99%